2019
DOI: 10.2174/1381612825666190712181403
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Immobilization on Nanomaterials for Biosensor and Biocatalyst in Food and Biomedical Industry

Abstract: Enzymes exhibit a great catalytic activity for several physiological processes. Utilization of immobilized enzymes has a great potential in several food industries due to their excellent functional properties, simple processing and cost effectiveness during the past decades. Though they have several applications, they still exhibit some challenges. To overcome the challenges, nanoparticles with their unique physicochemical properties act as very attractive carriers for enzyme immobilization. The enzyme immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 163 publications
0
8
0
Order By: Relevance
“…In contrast, the immobilized MS@MCL maintained 75.36% of enzyme activity after 8 weeks. Nanozyme immobilized to microspheres was more resistant to pH and heat inactivation mainly due to covalent bonding via amido linkage [ 25 ]. These results indicated that the nanozyme inside the microsphere could remain stable for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the immobilized MS@MCL maintained 75.36% of enzyme activity after 8 weeks. Nanozyme immobilized to microspheres was more resistant to pH and heat inactivation mainly due to covalent bonding via amido linkage [ 25 ]. These results indicated that the nanozyme inside the microsphere could remain stable for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…The present study was attempted to delineate the antibiofilm effect of N sativa essential oils against the pathogenic bacterium S aureus . In general, supplementation of N sativa oil in food products prevents hyperglycaemia and hypercholesterolemia 43 . Since it possesses the antimicrobial activity, it diminishes the microbial growth during food processing and storage as well as delays the oxidation of lipids in lipid containing foods.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cyanide-detoxifying ability of rhodanese has also been exploited to develop biosensors for cyanide detection [ 182 , 183 , 184 , 185 ]. A fundamental issue for optimal performance in biosensors is preserving the catalytic activity of the enzyme immobilized in bioelectronic devices [ 186 , 187 ]. De Araujo and colleagues have adsorbed rhodanese onto Langmuir–Blodgett (LB) monolayers of the phospholipid di-myristoyl-phosphatidic acid (DMPA), and characterized the enzyme-films by fluorescence spectroscopy, polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS), and atomic force microscopy.…”
Section: Biotechnological Application Of Tstmentioning
confidence: 99%